UNDERWATER WITH A HAND-LENS IN THE RIVERS OF CAPE HORN: ETHICAL VALUING OF FRESHWATER ECOSYSTEMS AND THEIR CO-INHABITANTS - Contador Mejias, Tamara Andrea; Rozzi Marin, Ricardo Roberto; Kennedy, James; Massardo Vega, Cristina Elvira Francisca; Ojeda Villarroel, Jaime Andrés; Caballero, Paula; Medina, Yanet; Molina, Rodrigo; Saldivia, Fernando; Berchez, Flavio; Stambuk, Andres; Morales, Veronica; et al. (My University, 2018)
The Cape Horn Biosphere Reserve (CHBR), is the largest one in Chile, and the only one that integrates marine and terrestrial ecosystems. It includes three national parks (NP): Cape Horn NP, Alberto de Agostini NP, and Yendegaia NP. The CHBR ; is immersed within the Magellanic sub-Antarctic ecoregion, which has been identified as one of the last pristine areas left in the world. Nonetheless, it is not free from local and global threats, such as invasive exotic species, climate change, massive tourism and other economic activities that do not value biological and cultural diversity. To contribute towards an appreciation of the values of biocultural diversity, the scientific team at Omora Park (Navarino Island, 55 degrees S), has developed the Field Environmental Philosophy (FEP) methodological approach, which integrates ecological sciences, arts, and environmental ethics through four interrelated steps: 1) interdisciplinary research, 2) poetic communication through the composition of metaphors, 3) design of field activities with an ethical and ecological orientation, and 4) in situ conservation, to contribute to biocultural conservation. We present the methods and results of a multidisciplinary work focused on invertebrates and freshwater ecosystems of the CHBR, with the aim to contribute: a) to a better understanding of the possible responses of aquatic insects to climate change in the long-term, and b) generate tools for research and education to ecologically and ethically value freshwater invertebrates and ecosystems. The conceptual foundations are based on the Land Ethics of Aldo Leopold, and the biocultural ethics of Ricardo Rozzi. Through the praxis of the FEP we generate concrete actions for the conservation of the natural and cultural heritage. Finally, we propose new research methodologies that include valuing of the invertebrates' lives. FEP provides a methodology that contributes towards the transformation of the prevalent way in which global society understands, values and relates to freshwater ecosystems and their co-inhabitants, fostering more respectful and sustainable life habits in the short and long term.
Keywords: insects; biocultural ethics; climate change; ecology; chile